Primeiro registro de Bunocephalus larai (Ihering, 1930) (Siluriformes, Aspredinidae) na bacia hidrográfica do rio Ivaí, alto rio Paraná, Brasil. - Aggio, José Lucas Toscano (2023)
Representatives of Aspredinidae are popularly known as banjo catfish due to their body shape. This family contains 13 recognized genera, all endemic to the Neotropical region. Bunocephalus Kner 1855 is the genus with the largest number of Aspredinidae species. This study reports the occurrence of Bunocephalus larai (Ihering, 1930) for the first time in the Ivaí river basin, as well as the expansion of distribution to latitudes south of the Paraná river basin. Four individuals were captured through electrofishing in the Muquilão River, a tributary of the Ivaí River, Paraná, Brazil, in a Conservation Unit in the municipality of Iretama. The records were obtained through an ichthyofaunistic inventory in the region. The four individuals were sampled in January 2022 (one individual), January (two individuals) and March (one individual) 2023. The distribution was recorded in the river basins of the upper Paraná River, in the Paranaíba, São Marcos, Capivari, Paraná rivers and Tibagi, the latter being the southernmost limit in the state of Paraná. Therefore, this study expands the distribution of B. larai to the Ivaí river basin and demonstrates the importance of ichthyofaunistic studies in headwater rivers to expand the distribution of this and other species.